Strategies for improving the solubility and metabolic stability of griseofulvin analogues - Petersen, Asger B.; Konotop, Gleb; Hanafiah, Nur Hafzan Md; Hammershøj, P.; Raab, Marc-Steffen; Krämer, Alwin; Clausen, M. H. (European journal of medicinal chemistry, 2016)
We report two types of modifications to the natural product griseofulvin as strategies to improve solubility and metabolic stability: the conversion of aryl methyl ethers into aryl difluoromethyl ethers at metabolic hotspots and the conversion of the C-ring ketone into polar oximes. The syntheses of the analogues are described together with their solubility, metabolic half-life in vitro and antiproliferative effect in two cancer cell lines. We conclude that on balance, the formation of polar oximes is the most promising strategy for improving the properties of the analogues.
Gesehen am 12.10.2020
Available online 28 March 2016